PATTERNS OF ATTENTION AND ENERGY CONSUMPTION CHANGES IN TWILIGHT DURING DRIVING URBAN STREETS: Array - Prasolenko, O.; Burko, D. (Municipal economy of cities. Series: «Economy science», 2020)
The dynamic process of movement of vehicles in cities is associated with interaction with objects of the road environment. Road conditions, traffic and pedestrians require certain actions from the driver to ensure road safety. Under such circumstances, the reliability and safety of road traffic in human-machine systems mainly depends on the functional state of the driver (provided that the technical component, the subsystem is “car”) and his ability to respond to changes in the traffic situation when obstacles arise (conflict situations). The development of states of tension and fatigue of the driver is associated with an increase in energy costs, which leads to a natural increase in the heart rate, respiration and other parameters indicating changes in the energy balance of the driver's body. Eye Tracking technology has been applied to detect attention. Energy costs were determined using a method that takes into account the frequency of the driver's external respiration when driving on the road and in the background. As a result, a model of change in the attention of drivers with driving experience and a model of energy consumption when driving in the evening twilight at a certain level of illumination were obtained. To determine the influence of conflict situations during movement in the evening twilight on the indicator of attention and energy consumption of the driver, a study was carried out in real conditions on city streets. A group of drivers with experience of 3-5 years and 10-16 years performed arrivals in the evening twilight on passenger cars "C" class. Experimental studies of the indicator of drivers' attention and functional state in conditions of evening twilight were carried out on different categories of city streets. The study involved drivers between the ages of 20 and 40. The obtained dependences of the change in the driver's functional state on illumination showed that at low illumination levels in the evening twilight, a rapid increase in the driver's functional state shifts. Thus, the energy consumption of the driver while driving depends on the types of conflict situations and the level of illumination. It was found that for drivers with less than 5 years of driving experience, shifts in functional state were more important than other drivers. Also, such drivers had lower attention indicators compared to experienced drivers with more than 10 years of driving experience. It was found that when the illumination changes at dusk, the energy consumption increases on average to 3.3 kcal / min for drivers with less than 5 years of experience, and for drivers with more than 10 years of experience, it increases by 2.4 kcal / min on average.